Response to Zhang et al. (2005): loss-of-function mutation in tryptophan hydroxylase-2 identified in unipolar major depression. Neuron 45, 11-16 - Glatt, Charles E; Carlson, Elaine; Taylor, Travis R; Risch, Neil; Reus, Victor I; Schaefer, Catherine A (Neuron (Cambridge, Mass.), 2005)
Because the authors selected older patients (>60 years) for their study, we cannot exclude that the A-allele is enriched due to an associated protective survival effect. [...]even with the strong functional data of which we do not doubt the quality, the report of a functional relevant genetic THP2 polymorphism associated with affective disorders is at this stage uncertain and needs to be replicated independently.